If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 33 + -4x Solving 5 = 33 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + 4x = 33 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + 4x = 33 + 0 5 + 4x = 33 Add '-5' to each side of the equation. 5 + -5 + 4x = 33 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 33 + -5 4x = 33 + -5 Combine like terms: 33 + -5 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 134.56/5.8+12=n | | 18-x=2x+3 | | 11x+3-3x-4-2x=7x-19-5x+26 | | -9x^2+4x+7=0 | | 5x+7=12x-7 | | 5x+-4=47 | | -7x^2+9x+2=0 | | 0.33+ln(x)=0 | | 28n=601 | | 0.0034=y-0.405 | | 230/36=n | | x^2+12x+144= | | 16=7 | | 45x^2-49x+98=0 | | (x^2+2)=2.6 | | 10x^2+10x+120= | | ln^2(x+1)-3ln(x+1)=-2 | | 121-x^2= | | ln^2(x+1)-3ln(x+1)+2=0 | | 12.30x=60 | | 60/12.30=n | | 9x^2-21x+6= | | -2x-5=-68+5x | | x+10=-4x+20 | | x^2+12x-288=0 | | 9-6x+7x=15 | | 2+5x-x=2 | | (4.5)(x)-(11)(1-x)=0 | | -4x-4+3x=-4 | | (1.5)(x)-(3)(1-x)=0 | | 4y-2y^2-1=0 | | 9x+34=74 |